2018
DOI: 10.6061/clinics/2018/e207
|View full text |Cite
|
Sign up to set email alerts
|

A didactic approach to presenting verbal and visual information to children participating in research protocols: the comic book informed assent

Abstract: OBJECTIVE:When children participate in research protocols, consent (by a parent or legal guardian) and assent (by the children) must be given. Understanding research protocols can be challenging for an adult and even more difficult for a child. The aim of this study was to describe the development of a comic book created to facilitate children's understanding of informed assent with clear and simple language.METHODS:Five researchers with scores above seven according to the Fehring criteria developed the comic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
(39 reference statements)
0
12
0
5
Order By: Relevance
“…This study was approved by the Uninorte Ethics Committee of the Barão do Rio Branco Faculty under protocol 1.996.775 and was conducted in accordance with the Declaration of Helsinki. Participants or their legal representatives (for minors) signed the informed consent form 26…”
Section: Participants and Methodsmentioning
confidence: 99%
“…This study was approved by the Uninorte Ethics Committee of the Barão do Rio Branco Faculty under protocol 1.996.775 and was conducted in accordance with the Declaration of Helsinki. Participants or their legal representatives (for minors) signed the informed consent form 26…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Massetti et al, developed a comic book with the goal of helping minors understand the concept of assent using illustrations and simple language (29). Twenty minors between the ages of 7 and 12 years, and who were participating in a trial to evaluate performance on a computational task (AKA the real study), were enrolled.…”
Section: Comic Booksmentioning
confidence: 99%
“…The comic book study's participants responded by using a Likert scale to score the clarity of the text and the illustrations. According to Massetti et al, most participants found the content of the comic book either "excellent" or "very good, " thus offering a viable option for obtaining informed assent (29).…”
Section: Comic Booksmentioning
confidence: 99%
“…Participants will be included if they have: the agreement to participate in the research from themselves [by signing assent form ( 33 )] and their legal guardians (by signing a consent form); a clinical diagnosis of CP will be carried out by a neuropaediatric clinician; with GMFCS levels I to IV and MACS I to IV; age ranging from 4 to 14 years.…”
Section: Methodsmentioning
confidence: 99%